2021
DOI: 10.1111/exd.14353
|View full text |Cite
|
Sign up to set email alerts
|

The effects of human dermal–derived mesenchymal stem cells on the keratinocyte proliferation and apoptosis in psoriasis

Abstract: Psoriasis is a common chronic inflammatory skin disease, characterized by epidermal hyperproliferation. Mesenchymal stem cells (MSCs) regulate inflammation and vascular proliferation in the psoriasis lesions. Whether dermal‐derived mesenchymal stem cells (DMSCs), the main MSCs in the dermis, regulate keratinocyte proliferation and apoptosis remains unknown. In the present study, we assessed the proliferation and apoptosis of keratinocytes cocultured with DMSCs isolated from either normal or psoriatic involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…1 D and F). In a previous study, necroptotic and apoptotic cell death was reported in skin lesions from patients with psoriasis [1] , [32] . Additionally, we analyzed the expression of the critical numbers involved in PANoptosis (pyroptosis) signaling in skin lesions of psoriatic patients.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…1 D and F). In a previous study, necroptotic and apoptotic cell death was reported in skin lesions from patients with psoriasis [1] , [32] . Additionally, we analyzed the expression of the critical numbers involved in PANoptosis (pyroptosis) signaling in skin lesions of psoriatic patients.…”
Section: Resultsmentioning
confidence: 93%
“…In psoriasis, evasion of keratinocyte apoptosis plays an important role in facilitating abnormal keratinocyte hyperproliferation [58] , [59] . Subsequently, various potential therapeutic strategies for psoriasis have emerged to promote keratinocyte apoptosis, such as miR-383 [18] , mesenchymal stem cells (MSCs) [32] , and BAY 11–7082 antagonists [60] . Necroptosis is a new type of programmed necrosis that can strongly facilitate the inflammatory response by inducing the manufacture of cytokines and disrupting damage-associated molecular pattern (DAMP) release [61] .…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes (KCs) play essential roles in both the initiation and maintenance phases of psoriasis since, being a part of the innate immune system, KCs are responsive to multiple triggers. There is mutual crosstalk between MSCs and KCs: on the one hand, high levels of pro-inflammatory cytokines secreted by MSCs induce KCs proliferation, probably via activating the PI3K/AKT signaling pathway [ 18 ] and through the secretion of cytokines such as Epidermal Growth Factor (EGF) [ 19 ] and inhibit their apoptosis due to the reduction in expression levels of caspase-3 [ 20 , 21 ]; it has also been observed that dermal PsO-MSCs contribute to the reduction in the cellular junction, with a consequent alteration in KC differentiation and shortened epidermal turnover time [ 22 , 23 ]. On the other hand, PsO-KCs co-cultured with control MSCs upregulates the expression of c-Myc, GLUT1, SCF, and EGF, resulting in enhanced metabolism and increased proliferation of MSCs, establishing a vicious cycle [ 24 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 16 Several recent studies have investigated the use of MSCs as a possible therapeutic option for psoriasis ( Table 1 ). 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 …”
Section: Stem Cell Therapy In Psoriasismentioning
confidence: 99%